DOKSA, KEKERASAN SIMBOLIK DAN HABITUS YANG DITUMPANGI DALAM KONSTRUKSI KEBUDAYAAN DI DEWAN KESENIAN JAKARTA - Zurmailis, Zurmailis; Faruk, Faruk (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
This research aims to reveal the doxa generated by the Jakarta Arts Council (DKJ)  and its role as the institution with the legitimacy to build cultural construction, especially in the field of literature. This study uses the theory of genetic structuralism or also known as constructivist structuralism by Pierre Felix Bourdieu. This theory departs from the basic concept of the habitus and the arena, agency and structure as the principles that gave birth and developed the habits, producing habitus as well as perspectives. The results shows that the habitus and the perspective place the Jakarta Arts Council as doxa and as a guidelines for cultural practices in art programs, which is rooted on the structure of culture that is constructed through symbolic violence toward the involved agents and is socialized in the field of culture through similarly of symbolic violence.